Adsorption and Photocatalytic Degradation of Crystal Violet Dye by using Cadmium Sulfide in Aqueous Solutions - Aseel M. Aljeboree (Journal of Global Pharma Technology, 2016)
Chemical methods were used to synthesized cadmium sulfide thin films in a mixed phase which testing for wastewater treatment through the photocatalytic degradation. Specific region of light (UV) was used to remove the organic pollutant which commonly destroy the environmental such Crystal violet dye forming what we could it wastewaters. The testing solutions were degraded under visible-light irradiation using the CdS thin films. Structural studies of the CdS photocatalyst refer to the hexagonal and cubic phases with good crystallinity and uniformly and homogenous distributed over all the sites of support with less agglomerations. The morphology analysis mostly shown induces porosity, which mostly enhance intercalating dyes. The optical band-gap energy of sample within film was 2.35 eV, which explained the high photcatalytic behavior in the degradation of the non-biodegradable Crystal violet dye. As accepted the semiconductor/ UV-light were succeed to declaration of day which shows good acceptable results. The surprised was the efficiency of degradation or deceleration was rises very high as compare with the same conditions of reaction in room temperature in addition to increases with raises of concentration from 0.5 to 4 g/L. Keywords: Cadmium sulfide, Photcatalytic degradation, Adsorption, Crystal Violet dye.